PENGARUH METODE RESITASI TERHADAP HASIL BELAJAR SISWA PADA TEMA INDAHNYA NEGERIKU KELAS IV SD NEGERI 6 SUWAWAL JEPARA - Diana Endah Handayani; Ana Ariyana (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2014)
This background of the research because the learning outcomes of students who are still under the KKM 70 because learning is monotonous, more teachers lecture so that students are less enthusiastic in participating in the learning process so that what the teacher was not well received by the students. The problems revealed in this study is there any method of recitation influence on learning outcomes of students on the theme of ?óÔé¼?ôindahnya negeriku?óÔé¼?Ø about student comprehension class IV 6 Suwawal Jepara? Goals to be achieved in this study was to determine the method of recitation is there any influence on student learning outcomes in the theme of ?óÔé¼?ôindahnya negeriku?óÔé¼?Ø about student comprehension class IV 6 Suwawal Jepara.This type research is quantitative. The population in this research is class IV in the SD Negeri 6 Suwawal Jepara. The samples taken were 40 learners using nonprobability sampling is a cluster sampling. The data in this study was obtained through the observation of observation of the activities of students to acquire value as well as on aspects of psychomotor tests to determine student learning outcomes in the cognitive aspects. The design in research is a pretest-posttest control group design.Based on the analysis of research data using the t-test is obtained t cognitive separated by 3,570; psychomotor tvalue 2,100 to 2,021 ttable for both the 5% significance level. So tvalue> ttable and H0 is rejected. Average increase cognitive learning outcomes for students class IV in SD Negeri 6 Suwawal Jepara before treatment was given by 45% and after the treatment was given at 100% and the average psychomotor learning outcomes which is 70%. Therefore, it can be concluded that there is a method of recitation influence on student learning outcomes theme of ?óÔé¼?ôindahnya negeriku?óÔé¼?Ø about student comprehension class IV SD Negeri 6 Suwawal Jepara.Suggestions made, namely to use the method of recitation should be in a class that number of students is not more than 25 students. That is because at this recitation method takes quite a long time, especially in the execution of duties and responsibilities.